Studies of variability in Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) through acorn protein profile analysis. - Valero Galván, José; Valledor, Luis; Navarro Cerrillo, Rafael M; Gil Pelegrín, Eustaquio; Jorrín-Novo, Jesús V (Journal of proteomics, 2011)
Studies of variability in Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.), the dominant tree species in the typical Mediterranean forest, have been carried out by using electrophoresis-based proteomic analysis of acorns. Ten populations distributed throughout the Andalusia region have been surveyed. Acorns were sampled from individual trees and proteins extracted from seed flour by using the TCA-acetone precipitation protocol. Extracts were subjected to SDS-PAGE and 2-DE for protein separation, gel images captured, spot or bands quantified, and subjected to statistical analysis (ANOVA, SOM and clustering). Variable bands or spots among populations were subjected to MALDI-TOF/TOF and LC-MS/MS for identification. The protein yield of the used protocol varied among populations, and it was in the 2.92-5.92 mg/g dry weight range. A total of 23 bands were resolved by SDS-PAGE in the 3-35 kDa Mr range, with 8 and 12, out of the total, showing respectively qualitative and quantitative statistically significant differences among populations. Data allowed grouping populations, with groups being correlated according to geographical location and climate conditions, to northern and southern, as well as the discrimination of both mesic and xeric groups. Acorn flour extracts from the most distant populations were analyzed by 2-DE, and 56 differential spots were proposed as markers of variability. Identified proteins were classified into two principal categories; storage and stress/defense protein. Besides providing the first reference map of mature acorn seeds, the use of SDS-PAGE and proteomics in characterizing natural biodiversity in forest trees will be discussed.
Keywords: Acorn proteomics; Chromatography; Electrophoresis; Gene Expression Profiling; Holm oak variability; Liquid; Mass; Matrix-Assisted Laser Desorpti; Plant Proteins; Plant Proteins: metabolism; Polyacrylamide Gel; Quercus; Quercus ilex proteomics; Quercus: genetics; Quercus: metabolism; Seeds; Seeds: chemistry; Spectrometry; Tandem mass spectrometry

Anaphylactic reaction to ingestion of Quercus ilex acorn nut - Vega; DomÍnguez; Cosmes; MartÍnez; BartolomÉ, B.; Palacios; Vega, a; Domínguez, C.; Cosmes, P.; Martínez, a; BartolomÉ, B.; Martínez, J.; et al. (Clinical & Experimental Allergy, 1998)
Background A patient experienced an anaphylactic reaction after eating acorn nuts, fruit of the holm oak (Quercus ilex), one of the most abundant trees in Spain. Several urticaria episodes upon ingestion of peanuts were also referred. Objective To assess the hypersensitivity reaction to acorn and to characterize the allergenic proteins involved. Methods Cutaneous tests were performed using the skin-prick technique, using a large variety of grass, tree and weed pollens as well as fresh nuts and nut extracts. Specific IgE determination was assessed by RAST. IgE binding bands were determined by SDS-PAGE immunoblotting. Results Skin-prick tests were strongly positive with acorn and peanut. Olea europaea, Quercus alba, Quercus ilex and grass pollens also elicited a weal higher than negative control. Patient serum had measurable levels of IgE antibodies especially to acorn, peanut and grass pollens. Only one protein band, of 17.9 kDa molecular mass, showed IgE-binding properties in the acorn extract. The possible homology of this strong allergenic protein with the group 1 tree pollen allergens was evidenced by the partial inhibition of the western blot with Bet v 1. Conclusions We present a case of anaphylaxis to acorn ingestion as demonstrated by in vivo and in vitro results. A 17.9 kDa IgE-binding band, showing some homology to group 1 pollen tree allergens, was recognized by patient serum.
The following values have no corresponding Zotero field: publisher: Blackwell Science Ltd, UK accession-num: 9677139
Keywords: acorn allergens; Anaphylaxis; Anaphylaxis: drug therapy; Anaphylaxis: etiology; Bet v 1; Cross Reactions; Electrophoresis; Food Hypersensitivity; Food Hypersensitivity: drug therapy; Food Hypersensitivity: etiology; Humans; Immunoblotting; Immunoglobulin E; Immunoglobulin E: blood; Male; Middle Aged; nut allergy; Nuts; Nuts: adverse effects; Nuts: immunology; Polyacrylamide Gel; Quercus ilex allergy; Radioallergosorbent Test; Skin Tests

Anaphylactic reaction to ingestion of Quercus ilex acorn nut - Vega; DomÍnguez; Cosmes; MartÍnez; BartolomÉ, B; Palacios; Vega, a; Domínguez, C; Cosmes, P; Martínez, a; BartolomÉ, B; Martínez, J; et al. (Clinical & Experimental Allergy, 1998)
Background A patient experienced an anaphylactic reaction after eating acorn nuts, fruit of the holm oak (Quercus ilex), one of the most abundant trees in Spain. Several urticaria episodes upon ingestion of peanuts were also referred. Objective To assess the hypersensitivity reaction to acorn and to characterize the allergenic proteins involved. Methods Cutaneous tests were performed using the skin-prick technique, using a large variety of grass, tree and weed pollens as well as fresh nuts and nut extracts. Specific IgE determination was assessed by RAST. IgE binding bands were determined by SDS-PAGE immunoblotting. Results Skin-prick tests were strongly positive with acorn and peanut. Olea europaea, Quercus alba, Quercus ilex and grass pollens also elicited a weal higher than negative control. Patient serum had measurable levels of IgE antibodies especially to acorn, peanut and grass pollens. Only one protein band, of 17.9 kDa molecular mass, showed IgE-binding properties in the acorn extract. The possible homology of this strong allergenic protein with the group 1 tree pollen allergens was evidenced by the partial inhibition of the western blot with Bet v 1. Conclusions We present a case of anaphylaxis to acorn ingestion as demonstrated by in vivo and in vitro results. A 17.9 kDa IgE-binding band, showing some homology to group 1 pollen tree allergens, was recognized by patient serum.
Keywords: acorn allergens; Anaphylaxis; Anaphylaxis: drug therapy; Anaphylaxis: etiology; Bet v 1; Cross Reactions; Electrophoresis; Food Hypersensitivity; Food Hypersensitivity: drug therapy; Food Hypersensitivity: etiology; Humans; Immunoblotting; Immunoglobulin E; Immunoglobulin E: blood; Male; Middle Aged; nut allergy; Nuts; Nuts: adverse effects; Nuts: immunology; Polyacrylamide Gel; Quercus ilex allergy; Radioallergosorbent Test; Skin Tests